Arya and other stories - Chandrika Balan (Hyderabad Oriental Blackswan, 2014)
She is from a village. She is angry at her conservative mother. She is a flawed activist. She is being judged. She makes compromises. She cannot die, even if she wills it. She chooses to command. Her children want to do away with her. She looks for friendships online. She craves for fame. She musters the courage to pursue her lover. What binds her through all these is her strength; she is indomitable. Arya and Other Stories is a collection of twelve short stories by Chandrika Balan, known in the Malayalam literary world as Chandramati. Balan brings to the reader a glimpse into the world of the woman in a village where feminism has reached. Here men know what feminism is, women know they can be independent; and, children know that their mother is not a caring-bearing machine. Balan$1 (Bs exploration is into the kind of questions a woman here goes through. Employing different writing styles realism, magic realism and postmodernism - Balan weaves a sensitive fabric that is a study of the contemporary woman. Accompanied by K. Satchidanandan$1 (Bs scholarly introduction that traces women$1 (Bs writing tradition in Kerala, this collection of poignant and incisive short stories is bound to interest every reader of fiction and translation Table of Contents Devigramam Arya Bonsai The People$1 (Bs Court The (Postmodern) Story of Jyoti Viswanath The Fifth One An Optical Illusion The Story of a Poem A Companion for the Twilight Hour Website Sponsors Please The Relevance of Graham Greene in the Life of a Brides
Keywords: English Fiction; English Novel; Malayalam Story Tr in English; Short Stories